Exploring mathematics concepts in Palestinian Keffiyeh motifs: An autoethnographic study - Fathir, Amrul Huda; Mariana, Neni; Dellarosa, Maretha; Gunansyah, Ganes; Alsulami, Naif Mastoor (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Culturally significant artifacts have long been recognized in ethnomathematics as sites where mathematical ideas are embedded and expressed through visual and symbolic forms. However, research remains limited on how such artifacts—particularly those originating beyond local classroom cultures—can be systematically analyzed to reveal mathematical structures relevant to school mathematics. Addressing this gap, the present study explores the mathematical concepts embedded in Palestinian Keffiyeh motifs and examines their potential relevance for mathematics learning, with a particular focus on geometry. Adopting a qualitative autoethnographic approach, the study draws on narrative writing and dialogic engagement with relevant literature to examine recurring structural patterns within Keffiyeh designs. The analysis identifies three central mathematical structures: tessellation generated through geometric transformations, hierarchical composition of planar shapes, and layered symmetry operating at both global and sub-unit levels. To enhance interpretive rigor and curricular alignment, an in-depth interview was conducted with a mathematics education expert to validate the identified mathematical interpretations and clarify their correspondence with school-level geometry concepts. The findings suggest that Keffiyeh motifs exemplify sophisticated geometric organization and reveal cross-cultural commonalities in mathematical patterning found in culturally meaningful artifacts. From a pedagogical perspective, these motifs offer rich contexts for geometry instruction through visualization tasks, construction and decomposition activities, and formative assessment of students’ geometric reasoning. While the study does not provide empirical classroom-based evidence, it contributes conceptually and methodologically to ethnomathematics by demonstrating how reflective and dialogic inquiry can be used to systematically uncover mathematical meaning in cultural artifacts. Limitations related to interpretive subjectivity are acknowledged, and directions for future classroom-based and cross-cultural research are outlined.